Le Livre de la jungle - Rudyard Kipling (Open Library, 1894)
Saved from the jaws of the evil tiger Shere Khan, young Mowgli is adopted by a wolf pack and taught the law of the jungle by lovable old Baloo the bear and Bhageera the panther. The adventures of Rikki-Tikki-Tavi the snake-fighting mongoose, little Toomai and the elephantýs secret dance, and Kotick the white seal are all part of Mowgliýs extraordinary journey with his animal friends.Christopher Paolini is the author of the award-winning Inheritance cycle books, including Eragon.
Droits : Métadonnées bibliographiques et couvertures référencées via Open Library / Internet Archive. Vérifier les droits de couverture selon usage final.
Keywords: jungle; animaux; Kipling; classique; Littérature